ChemInform Abstract: One‐Step Construction of Saturated Six‐Membered Rings Directly Using Calcium Carbide as an Acetylene Source: Synthesis of 1, 3, 5‐Triaroylcyclohexanes. Issue 35 (August 2016) - Li, Zheng; He, Lili; Fu, Rugang; Song, Geyang; Song, Wenli; Xie, Demeng; Yang, Jingya
Abstract: The title cyclohexanes are efficiently prepared from various aromatic and heteroaromatic aldehydes without use of precious transition metal catalysts, and flammable and explosive gas.